Posterior scleritis mimicking indirect carotid-cavernous fistula - Tan , A.K; Premsenthil, M.; Salowi, M.A; Asok, T.; Gudom, I (The Internet Journal of Ophthalmology and Visual Science, 2009)
Tan Aik Kah, Mallika Premsenthil, Mohamad Aziz Salowi, Asokumaran Thanaraj & Intan ak Gudom